Pollen collection, colony development and environmental parameters in Scaptotrigona hellwegeri bees (Hymenoptera: Meliponini) - Contreras-Escareño, Francisca; Betancourt-Sánchez, Andrea Judith; Macias-Macias, José Octavio; Tapia-González, José María; Tapia-Rivera, José Carlos; Guzmán-Novoa, Ernesto (Ecosistemas y Recursos Agropecuarios, 2023)
Pollen collection, the influence of environmental parame- ters and weight gain in Scaptotrigona hellwegeri colonies were studied. The entry of bees with pollen was recorded for 5 min every hour during the day, biweekly for 9 months. The starting and ending time and period of the day during which, the bees collected more pollen were determined. The environmental parameters were related to pollen collection and the colonies were weighed monthly. The starting and ending times of pollen collection were at 8:00 a.m. and 9 p.m., with a collection peak between 11:00 a.m. and 5:00 p.m. Temperature, light intensity, relative humidity, and wind speed had a moderate relationship with collection activity. The colonies slightly increased in weight in January, and a higher collection of pollen was observed in January and May.
Keywords: Scaptotrigona hellwegeri; pollen collection; weight gain; environmental parameters; growth colonies.